Preschool educators’ pre-numerical skill pedagogical challenges - Julianty Idris; Norly Jamil; Arulmozhi Narayanasamy (Intelektual Pustaka Media Utama, 2026)
The current study seeks to determine the challenges encountered by preschool educators’ pre-numerical skill pedagogical challenges. A qualitative approach, namely interviews, was employed and conducted among six experienced preschool teachers to acquire in-depth insights into the challenges encountered in inculcating pre-numerical skills. The six respondents were recruited via purposive sampling, namely maximum variation sampling, to fulfil specific criteria. Four primary themes were revealed, namely i) Theme 1: teachers lack specific guidance due to the highly general Kurikulum Standard Prasekolah Kebangsaan (KSPK); ii) Theme 2: students from low socioeconomic backgrounds exhibit deficiencies in pre-numerical knowledge; iii) Theme 3: teachers demonstrate an insufficient competence in pre-numerical teaching pedagogies; and iv) Theme 4: an inadequate awareness among teachers regarding the importance of pre-numerical skills exists. The implications highlighted the requirement for tailored support and training to improve preschool teachers’ pre-numerical skill pedagogies. The findings also contributed to the curricular improvement to assist preschool educators in providing more effective pedagogical practices, especially pre-numerical skills. Future scholars can conduct a more in-depth investigation of effective teaching strategies and interventions to aid students from low socioeconomic backgrounds in mastering pre-numerical competencies.